Effects of standard of care drugs and resolvin D2 on cellular senescence in pulmonary fibrosis - Garcia, Stephanie Badaró (2022)
Cellular senescence is pivotal in idiopathic pulmonary fibrosis (IPF) progression. Still, it is yet unknown the effects of standard-of-care (SOC) drugs nintedanib and pirfenidone on senescence lung fibroblasts. In addition, specialized pro-resolving lipid mediators have been shown to be effective at improving infection clearance and hold strong therapeutic potential in the management of COVID-19. However, its mechanisms of action on proliferative and senescent fibroblasts were not yet explored. In this study, we elucidated the effects of SOC drugs on senescent normal and IPF lung fibroblasts in vitro and the effects of Resolvin D2 on proliferative and senescent lung fibroblasts from normal and IPF patients. Colorimetric/fluorimetric assays, qRT-PCR, and western blotting were used to evaluate the effect of SOC drugs on senescent normal and IPF lung fibroblasts. SOC drugs did not induce apoptosis without death ligands in normal or IPF senescent cells. SOC drugs increased caspase-3 activity in the presence of FasL in normal but not in IPF senescent fibroblasts. Conversely, nintedanib enhanced Bcl-2 expression in senescent IPF lung fibroblasts. Moreover, in senescent IPF cells, pirfenidone alone induced MLKL phosphorylation, provoking necroptosis. In addition, fragmented gasdermin D, indicating pyroptosis, was not detected under any condition. In addition, SOC drugs increased transcript levels of fibrotic and senescence markers in senescent IPF fibroblasts, whereas D+Q inhibited all these markers. Finally, D+Q enhanced GDF15 transcript and protein levels in both normal and IPF senescent fibroblasts. Conversely, RvD2 drugs significantly decrease transcript levels of BIRC5, CCR10, COL1A1, COL3A1, FN1, GDF15, and WNT16 in senescent IPF fibroblasts. However, further studies are necessary to elucidate the therapeutic implications of RvD2 in IPF fully.